Digital transformation of museums: A new approach to cultural heritage conservation and inheritance - Lyu, Dan (Transactions on Social Science, Education and Humanities Research, 2024)
With the rapid development of information technology, digital transformation has become a key measure for museum industry to improve service quality and enhance cultural influence. However, in the actual process of progress, museum digital transformation still facesmany challenges. This paper discusses the importance of museum digital transformation in the protection and inheritance of cultural heritage and the concrete implementation path. Through in-depth research on the application of digital technology in museum work, this paper proposes the necessity, implementation strategy and challenges of digital transformation. Research shows that digital transformation can notonly improve the operational efficiency and visiting experience of museums, but also promote the wide dissemination and in-depth research of cultural heritage.